Navigating need: Mark 6:30–44. (August 2019) - Weaks, Dawn Darwin
In society's 24/7 news cycle, caring people can easily become overwhelmed with the needs of this world, in addition to the needs of family, friends, and self. This sermon explores one of the most-told stories of the New Testament, the miraculous feeding of thousands, specifically the account in Mark 6:30–44. It outlines three potential responses to meeting needs: engorging, exhausting oneself, and engaging. The sermon celebrates the radically alternative way of Jesus to meet needs miraculously, as it offers a hopeful word about how Christians can navigate need faithfully, responsively, and expectantly.